2004
DOI: 10.1158/1078-0432.ccr-04-0683
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ovarian Cancer

Abstract: Ovarian cancer is increasingly recognized as a chronic disease whose treatment is often characterized by administration of multiple, sequential active agents, each of which may or may not be accompanied by a tumor response. Despite the large proportion of patients who relapse and undergo longer-term treatment, the question of optimal treatment duration has not been fully addressed to date. For patients who progress on therapy, the answer is straightforward: they are switched to another active agent, presumably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 86 publications
0
71
0
1
Order By: Relevance
“…This brings into question the traditional strategy of limiting treatment to six to eight cycles and begs the potential benefit of extended treatment and symptom palliation until disease progression in patients who achieve a partial response or sta- ble disease. Treating until disease progression may allow for better disease management with the limited therapeutic options available in women with ovarian cancer [30]. While this approach may not be appropriate when using toxic regimens with intensive administration requirements (e.g., platinum-taxane combinations), it can be accomplished with less toxic agents with extended administration intervals (e.g., PLD).…”
Section: Discussionmentioning
confidence: 99%
“…This brings into question the traditional strategy of limiting treatment to six to eight cycles and begs the potential benefit of extended treatment and symptom palliation until disease progression in patients who achieve a partial response or sta- ble disease. Treating until disease progression may allow for better disease management with the limited therapeutic options available in women with ovarian cancer [30]. While this approach may not be appropriate when using toxic regimens with intensive administration requirements (e.g., platinum-taxane combinations), it can be accomplished with less toxic agents with extended administration intervals (e.g., PLD).…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited success in treating recurrent disease up to now, recent studies have suggested treating ovarian cancer as a ''chronic disease'' (10). These studies advocate the early detection of recurrent disease, enabling the use of lower doses of chemotherapeutic agents to control disease progression, although the results of these studies on the effect on survival are still awaited.…”
mentioning
confidence: 99%
“…The response rates have varied from 7% to 25% (17,18), and the incidence of Grade 4 toxicity (19) has not been negligible (10,20). The review by Salom et al (10) included information on new products and ongoing trials but did not, surprisingly enough, mention RT at all.…”
Section: Discussionmentioning
confidence: 99%